APPLICATION OF GALAWI TRAFFIC MANAGEMENT &COMMAND CENTER(GTMCC) TO IMPROVE THE EFFICIENCY OFPUBLIC SERVICES IN TEGAL POLICESTATION - Umar Ma'ruf; Muhammad Adil Aristo (UNISSULA, 2020)
This study aims to determine and analyze: Description GTMCC of Tegal Police Station, Factors that influence the application GTMCC of Tegal Police Station, and implementation of Galawi Traffic Management & Command Center (GTMCC) can improve the efficiency of public services at Tegal Police Station. The approach method used is empirical juridical. The data used is secondary data(legal material) and primary data, i.e. data from the field. Data were then analyzed qualitatively and presented descriptively analytically. Research conclusions: (1)GTMCC is a form of public service of the police with centralized control that will facilitate the elements of the Tegal Police Station leadership in the process of monitoring and evaluating the handling of public complaints. Applications in GTMCC consist of Sipoci, GPS, TMC, IMM, Website, and Social Media, and RLR; (2)Factors of affecting the implementation of GTMC Tegal Police consist of human factors, services, budget, and infrastructure; (3)Application GTMCC increases the efficiency of public services in the Tegal Police Station more effective access, quality services, better and more efficient processes, systems and communication, more transparent and faster decision making, and a more empowered community.